Glucocorticoids in the treatment of non-infectious superior ophthalmic vein thrombosis – Three cases and a review of the literature - Samuel Sigurdsson; Elin Bohman; Frank Träisk; Urszula Arnljots (American Journal of Ophthalmology Case Reports, 2024)
Purpose: Superior ophthalmic vein thrombosis (SOVT) is a rare clinical entity, which can have a septic and an aseptic cause. Aseptic SOVT is typically treated with anticoagulation. Glucocorticoids are reserved for cases with concurrent orbital inflammation.We present three cases of SOVT due to carotid cavernous fistula not responding to standard treatment, subsequently successfully treated with glucocorticoids. Observations: Three patients with various degrees of proptosis, ophthalmoplegia, orbital stasis and reduced vision are presented. One patient was confirmed to have isolated SOVT, while the other two had associated cavernous sinus thrombosis. All patients had underlying carotid-cavernous fistula without signs of infection. All patients were initially treated with parenteral anticoagulation. Two patients were treated with intraocular pressure-reducing medication. One of whom underwent canthotomy-cantholysis. Two patients experienced a gradual worsening of symptoms during treatment with anticoagulation, while one patient improved before deteriorating. All patients received additional treatment with glucocorticoids consisting of a three-day treatment with intravenous methylprednisolone 500 mg, followed by oral glucocorticoids resulting in total regression of symptoms. Two patients regained 20/20 vision, with some vision field defects, while the third patient regained 20/25 vision. Conclusion and importance: The addition of glucocorticoids in the treatment of aseptic SOVT can lead to improvement of symptoms and a potentially better prognosis. However, the risk of complications of glucocorticoid treatment must be carefully considered on a case-by-case basis.